Crystal structure of N-(3,4-dichlorobenzylidene)-4-methylaniline, C14H11Cl2N - Yuan Hua; Chen Chunni; Wang Linyan (Zeitschrift für Kristallographie - New Crystal Structures, 2017)
C14H11Cl2N, monoclinic, P21/c (no. 14), a = 6.1494(3) Å, b = 14.4196(5) Å, c = 14.2686(8) Å, β = 97.055(5)°, V = 1255.64(10) Å3, Z = 4, Rgt(F) = 0.0347, wRref(F2) = 0.0894, T = 290 K.